An Efficient CaO‐Based Catalyst for Rapid Production of Biodiesel without Glycerol as a by‐Product Using a Tri‐Component Reaction. (4th October 2018) - Tang, Ying; Li, Shaoying; Dong, Jianlong; Meng, Mei; Zhang, Jie
Abstract: In this work, commercial CaO was modified using various sodium salts (Na2 WO4, Na2 CO3, Na2 SO4, and NaCl), among which NaCl/CaO showed the best catalytic performance for no‐glycerol biodiesel production using three components of rapeseed oil, dimethyl carbonate (DMC), and methanol as reactants. 97.1% biodiesel yield was obtained at 1 h in the presence of NaCl/CaO. Various techniques including N2 physical adsorption, XRD, and CO2 ‐chemical adsorption revealed that the unique catalytic activity of NaCl/CaO was related to its higher degree of crystallinity and relatively weaker surface basicity, and large pore size in the structure compared to other catalysts. Furthermore, it was found that the rapid hydration by impregnation of CaO can be greatly weakened in the presence of NaCl and the pore diameter plays a more important role than the basicity of solid catalysts in this heterogeneous transesterification.